Ameloblastic fibro-odontoma: A case report - Cavalcante, Ana-Sueli-Rodrigues [UNESP]; Anbinder, Ana-Lia [UNESP]; Costa, Nivea-Cristina-Sena [UNESP]; Lima, Jose-Roberto Sa; Carvalho, Yasmin-Rodarte [UNESP] (Medicina Oral S L, 2009)
Ameloblastic fibro-odontoma (AFO) is a rare, benign, slow-growing odontogenic tumor, generally asymptomatic and more prevalent in children and adolescents. We report a case of AFO in the mandible of an eight-year-old Caucasian male patient, and review the literature. Intraoral examination revealed a swelling extending from the deciduous second molar to the retromolar triangle, covered with normal mucosa. A panoramic radiograph showed a large, well-demarcated radiolucency with radiopaque areas. The provisional diagnosis was of AFO, and so an incisional biopsy was performed. Histologically, the lesion was composed of connective tissue resembling the dental papilla, with epithelial strands or islands, as well as denticles and amorphous masses of enamel and dentin consistent with a diagnosis of AFO. Surgical excision and curettage of the lesion were performed. The patient has been monitored for eight years and the lesion has not recurred.
Keywords: Odontogenic tumors; odontoma; fibro-odontoma; ameloblastic